Displacement measurement using a unique digital camera - Pereira, João Antonio [UNESP]; Sabino, Danilo Damasceno [UNESP]; Turra, Antonio Eduardo [UNESP] (Trans Tech Publications, 2014)
This paper presents a noncontact technique for displacement measurement based on the variation of the pixels positions of a target object in the images captured by CCD or CMOS sensor. A video from a moving structure is madeand then it is analyzed frame by frame and the variation of the pixels position of the target object in the structure is calculated for each frame and related with the position of the object in the image.The proposed approach is evaluated to measuring vibrations of a reduced scale model of two-floor building lab structure,which focuses on the advantage of using a unique camera for measurements of structural vibrations. The results obtained are comparedto reference model and have shown good agreement. © (2014) Trans Tech Publications, Switzerland.
Keywords: Digital cameras; Measurement; Noncontact; Vibration analysis